2021
DOI: 10.7554/elife.60126
|View full text |Cite
|
Sign up to set email alerts
|

Autoregulatory control of microtubule binding in doublecortin-like kinase 1

Abstract: The microtubule-associated protein, doublecortin-like kinase 1 (DCLK1), is highly expressed in a range of cancers and is a prominent therapeutic target for kinase inhibitors. The physiological roles of DCLK1 kinase activity and how it is regulated remain elusive. Here, we analyze the role of mammalian DCLK1 kinase activity in regulating microtubule binding. We find that DCLK1 autophosphorylates a residue within its C-terminal tail to restrict its kinase activity and prevent aberrant hyperphosphorylation within… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 58 publications
3
30
0
Order By: Relevance
“…After spines are produced, there may be a temporally regulated shift of NrCAM binding from DCLK1 to Ankyrin, possibly regulated by tyrosine dephosphorylation of NrCAM at the FIGQY motif. With respect to additional modes of DCLK1 regulation, recent research has shown that DCLK1 autophosphorylates on its carboxyl terminal tail, which inhibits microtubule binding (Agulto et al, 2021). Future studies with the Nex1Cre-ERT2: DCLK1 flox/flox : RCE mice will be aimed at determining if loss of DCLK1 from pyramidal neurons impairs excitatory transmission or behavior due to reduction of spine density on apical dendrites of cortical pyramidal neurons in the prefrontal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…After spines are produced, there may be a temporally regulated shift of NrCAM binding from DCLK1 to Ankyrin, possibly regulated by tyrosine dephosphorylation of NrCAM at the FIGQY motif. With respect to additional modes of DCLK1 regulation, recent research has shown that DCLK1 autophosphorylates on its carboxyl terminal tail, which inhibits microtubule binding (Agulto et al, 2021). Future studies with the Nex1Cre-ERT2: DCLK1 flox/flox : RCE mice will be aimed at determining if loss of DCLK1 from pyramidal neurons impairs excitatory transmission or behavior due to reduction of spine density on apical dendrites of cortical pyramidal neurons in the prefrontal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we and others have shown that the DCLK1 kinase domain negatively regulates microtubule polymerization, at least in vitro , and the C-terminal autoinhibitory domain (AID) of DCLK1 competes with ATP for access to the catalytic kinase domain of DCLK1, thus negatively regulating the kinase activity of DCLK1 ( 29, 31, 54 ). Notably, cancer-associated mutations in the AID domain lead to elevated kinase activity and reduced microtubule binding ( 54, 55 ). Both full-length and short isoforms have documented pro-EMT and pro-cancer functions and their kinase activity is blocked by DCLK1-IN-1 ( 30, 5658 ).…”
Section: Discussionmentioning
confidence: 99%
“…DCLK1 also autophosphorylates its C terminus at T688 residue to block hyperphosphorylation of N-terminal doublecortin domains. Hypophosphorylated and unphosphorylated doublecortin domains bind microtubules with higher affinity ( 49 ). Inhibition of T688 phosphorylation by DCLK1-IN-1 can disrupt DCLK1 interactions with microtubules and inhibition of the movement of viral RNA replication complexes.…”
Section: Discussionmentioning
confidence: 99%